Species composition and distribution patterns of early life stages of cephalopods at Great Meteor Seamount (subtropical NE Atlantic) - Diekmann, Rabea; Piatkowski, Uwe (Urban & Fischer, 2004)
The distribution of early life stages of cephalopods was studied during a cruise of RV Meteor in September 1998 at Great Meteor Seamount, an isolated flat-topped seamount in the subtropical eastern North Atlantic. Zooplankton sampling was conducted with a multi-opening-closing net (modified MOCNESS, 1 m² net opening, 335 µm mesh size) in seven depth strata between 290 m depth and the surface. 1180 early life stages of cephalopods were collected, representing at least 18 families and 31 mainly oceanic species. Most of the identified cephalopods comprised mesopelagic species (e. g., representatives of the families Enoploteuthidae and Pyroteuthidae) that showed diel vertical migration patterns. Hydrographic measurements parallel to zooplankton sampling revealed slow anticyclonic recirculation around the seamount forming a Taylor column and, thus, some retention potential for passive particles. Nevertheless, multivariate statistical analysis revealed no differences in the cephalopod community between the area in the proximity of the summit and the adjacent oceanic region. This was partly related to the depth of the plateau (< 300 m), which resulted in only slightly enhanced primary production, as well as to the low retention potential for active vertical migrators. However, reduced numbers of cephalopods were observed over the summit in night-time sampling, indicating gap formation above the seamount.